Anatomically grounded estimation of hindlimb muscle sizes in Archosauria. Issue 2 (7th October 2022) - Cuff, Andrew R.; Wiseman, Ashleigh L. A.; Bishop, Peter J.; Michel, Krijn B.; Gaignet, Raphäelle; Hutchinson, John R.
Abstract: In vertebrates, active movement is driven by muscle forces acting on bones, either directly or through tendinous insertions. There has been much debate over how muscle size and force are reflected by the muscular attachment areas (AAs). Here we investigate the relationship between the physiological cross‐sectional area (PCSA), a proxy for the force production of the muscle, and the AA of hindlimb muscles in Nile crocodiles and five bird species. The limbs were held in a fixed position whilst blunt dissection was carried out to isolate the individual muscles. AAs were digitised using a point digitiser, before the muscle was removed from the bone. Muscles were then further dissected and fibre architecture was measured, and PCSA calculated. The raw measures, as well as the ratio of PCSA to AA, were studied and compared for intra‐observer error as well as intra‐ and interspecies differences. We found large variations in the ratio between AAs and PCSA both within and across species, but muscle fascicle lengths are conserved within individual species, whether this was Nile crocodiles or tinamou. Whilst a discriminant analysis was able to separate crocodylian and avian muscle data, the ratios for AA to cross‐sectional area for all species and most muscles can be represented by a single equation. The remaining muscles have specific equations to represent their scaling, but equations often have a relatively high success at predicting the ratio of muscle AA to PCSA. We then digitised the muscle AAs of Coelophysis bauri, a dinosaur, to estimate the PCSAs and therefore maximal isometric muscle forces. The results are somewhat consistent with other methods for estimating force production, and suggest that, at least for some archosaurian muscles, that it is possible to use muscle AA to estimate muscle sizes. This method is complementary to other methods such as digital volumetric modelling. Abstract : Digitised muscle attachment areas from the hindlimbs of Nile crocodiles, tinamous and four other birds were used to estimate muscle physiological cross‐sectional areas. Some significant relationships were found, so it was deemed justifiable to estimate these areas in the theropod dinosaur Coelophysis, obtaining some different values from other studies'. This method is complementary to others such as volumetric 3D reconstruction.